2016
DOI: 10.3389/fimmu.2016.00344
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect against Extracellular Histones Afforded by Long-Pentraxin PTX3 as a Regulator of NETs

Abstract: Pentraxin 3 (PTX3) is a soluble pattern recognition molecule that plays critical roles in innate immunity. Its fundamental functions include recognition of microbes, activation of complement cascades, and opsonization. The findings that PTX3 is one of the component proteins in neutrophil extracellular traps (NETs) and binds with other NET proteins imply the importance of PTX3 in the NET-mediated trapping and killing of bacteria. As NETs play certain critically important host-protective roles, aberrant NET prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 85 publications
(118 reference statements)
0
31
0
Order By: Relevance
“…It is hypothesized that PTX3 may act to protect against the adverse consequences of NETs by binding circulating histone, thereby preventing endothelial injury and acting as an antiinflammatory mediator in patients undergoing cardiac surgery. 44,45 We observed that the PTX3 level increased during the perioperative period and reached abnormal levels (> 2000 pg/mL) after CPB, but did not reach high levels commonly seen in sepsis (> 14,000 pg/mL). 46,47 Additionally, we found no correlations between PTX3 and NETs measurements during the perioperative period.…”
Section: Discussionmentioning
confidence: 74%
“…It is hypothesized that PTX3 may act to protect against the adverse consequences of NETs by binding circulating histone, thereby preventing endothelial injury and acting as an antiinflammatory mediator in patients undergoing cardiac surgery. 44,45 We observed that the PTX3 level increased during the perioperative period and reached abnormal levels (> 2000 pg/mL) after CPB, but did not reach high levels commonly seen in sepsis (> 14,000 pg/mL). 46,47 Additionally, we found no correlations between PTX3 and NETs measurements during the perioperative period.…”
Section: Discussionmentioning
confidence: 74%
“…132,133 NETs have tissue-damaging and thrombogenic actions, at least partially mediated by histones. The ability of PTX3 to quench the potentially deleterious actions of histones [134][135][136] raises the interesting possibility that not all NETs are created equal, but that the rate of association with innate immune signals might modify their impact on the microenvironment. Further studies in vitro and in patients' tissues (see below) are necessary to validate this hypothesis.…”
Section: Ptx3 In the Response To Tissue Damage And Repairmentioning
confidence: 99%
“…Neutralization of extracellular histones has been reported to be protective in various inammatory conditions. 21,22 Here we investigated whether heparin, which is able to bind histones, 23 would diminish the observed effects of histones on the cells. Antihistone H4 antibody was applied as the control.…”
Section: Extracellular Histones Provoked Cytotoxicity and Cytokine Prmentioning
confidence: 99%